Changes in plasma half-life and clearance of 3H-25-hydroxyvitamin D3 in patients with intestinal malabsorption. Issue 12 (December 1982) - Batchelor, A J; Watson, G; Compston, J E
Abstract : The plasma disappearance of intravenously administered tracer doses of tritium-labelled 25-hydroxyvitamin D3 (25OHD3) wa studied in six normal subjects and in 15 patients with intestinal malabsorption. The plasma half-life was significantly shorter and the clearance rate significantly greater in the group with malabsorption compared with the controls. One explanation for this increased elimination could be interruption of an enterohepatic circulation of 25OHD occurring in subjects with malabsorption and such a mechanism could account for the loss of endogenous vitamin D in these patients.